Structural Characterization of Arginine Vasopressin and Lysine Vasopressin by Fourier-Transform Ion Cyclotron Resonance Mass Spectrometry and Infrared Multiphoton Dissociation. Issue 3 (June 2015) - Bianco, Giuliana; Battista, Fabio G.; Buchicchio, Alessandro; Amarena, Concetta G.; Schmitt-Kopplin, Philippe; Guerrieri, Antonio
Arginine vasopressin (AVP) and lysine vasopressin (LVP) were analyzed by reversed-phase liquid chromatography mass spectrometry using Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometry (MS) electrospray ionization (ESI) in the positive ion mode. LVP and AVP exhibited the protonated adduct [M + H] + as the predominant ion at m/z 1056.43965 and at m/z 1084.44561, respectively. Infrared multiphoton dissociation (IRMPD), using a CO2 laser source at a wavelength of 10.6 μm, was applied to protonated vasopressin molecules. The IRMPD mass spectra presented abundant mass fragments essential for a complete structural information. Several fragment ions, shared between two target molecules, are discussed in detail. Some previously unpublished fragments were identified unambiguously utilizing the high-resolution and accurate mass information provided by the FT-ICR mass spectrometer. The opening of the disulfide loop and the cleavage of the peptide bonds within the ring were observed even under low-energy fragmentation conditions. Coupling the high-performance FT-ICR mass spectrometer with IRMPD as a contemporary fragmentation technique proved to be very promising for the structural characterization of vasopressin.